Rancang Bangun Dan Analisis Usability Website Badan Usaha Penerbit Kampus - Rivalta Luxyana Nur hikmah; Tegar Restiana; Uuf Brajawidagda (Politeknik Negeri Batam, 2020)
Introducing a product certainly requires a medium or intermediary so that the product can be known by the wider community. One of the most frequently used media nowadays is the website or marketing site. The main purpose of this website is to promote products that have been made based on the works of the authors to be better known to the wider community. A website must also be user-friendly, easy to understand, access, remember, and provide useful information to its users. The creation of this website uses the Web Development Life Cycle (WDLC) method, the website will be tested using the usability model which is a qualitative analysis to determine how easy the user is using the interface of an application. The data collection techniques will use the interview technique, with the determination of the sample with purposive sampling technique. The Data obtained later will be analyzed and tested validity with techniques found in qualitative research methods.